Terminal Diazirines Enable Reverse Polarization Transfer from 15N2 Singlets. (3rd July 2019) - Zhang, Guannan; Colell, Johannes F. P.; Glachet, Thomas; Lindale, Jacob R.; Reboul, Vincent; Theis, Thomas; Warren, Warren S.
Abstract: Diazirine moieties are chemically stable and have been incorporated into biomolecules without impediment of biological activity. The 15 N2 labeled diazirines are appealing motifs for hyperpolarization supporting relaxation protected states with long‐lived lifetimes. The (‐CH 15 N2 ) diazirine groups investigated here are analogues to methyl groups, which provides the opportunity to transfer polarization stored on a relaxation protected (‐CH 15 N2 ) moiety to 1 H, thus combining the advantages of long lifetimes of 15 N polarization with superior sensitivity of 1 H detection. Despite the proximity of 1 H to 15 N nuclei in the diazirine moiety, 15 N T 1 times of up to (4.6±0.4) min and singlet lifetimes T s of up to (17.5±3.8) min are observed. Furthermore, we found terminal diazirines to support hyperpolarized 1 H2 singlet states in CH2 groups of chiral molecules. The singlet lifetime of 1 H singlets is up to (9.2±1.8) min, thus exceeding 1 H T 1 relaxation time (at 8.45 T) by a factor of ≈100. Abstract : Überlegene Empfindlichkeit über lange Zeiträume : Die terminale Diaziringruppe ist ein vielversprechender molekularer Marker, die den Transfer von in einer relaxationsgeschützten (CH 15 N2 )‐Gruppe gespeicherter Hyperpolarisation auf 1 H ermöglicht. Die Methode kombiniert so die Vorteile der langen Lebensdauer der 15 N‐Polarisation mit der überlegenen Empfindlichkeit der 1 H‐Detektion.